Rheological evolution of straw-cattle manure (SCM) treated by dry anaerobic digestion in batch and in continuous pilot reactors - Hernandez-Shek, M A (Waste management (New York, N.Y.), 2022)
Copyright © 2022 Elsevier Ltd. All rights reserved.